2017
DOI: 10.1111/jfbc.12450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A biofortification on the nutritional composition of cassava flour (gari) and evaluation of its glycemic index in healthy adults

Abstract: The nutritional and anti-nutritional compositions of cassava flour (gari) processed from white (TMS 30572) and vitamin A-biofortified yellow (TMS 07/0593) cassava cultivars were evaluated using standard methods. In addition, the glycemic index (GI) of eba (local food made from the two gari samples) was also evaluated. The yellow gari had significantly higher crude fiber and sugar but lower starch contents compared to the white gari. Similarly, b-carotene (7.34 mg/g) and total carotenoids (13.10 mg/g) levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…[ 27 ] Many studies have reported the lack of protein in banana flour and cassava flour. [ 28,29 ] However, no study has defined the protein quality of these flours that is further discussed later in the amino acid profiles section.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] Many studies have reported the lack of protein in banana flour and cassava flour. [ 28,29 ] However, no study has defined the protein quality of these flours that is further discussed later in the amino acid profiles section.…”
Section: Resultsmentioning
confidence: 99%
“…Okafor et al (), who worked on bread making found that cassava flour substitution of wheat flour of up to 30% did not have a significant effect on the glycemic index of bread. However, it has been debated that most the cassava varieties have high glycemic properties so its utilization in food products must be selected carefully (Astuti, Hendriyani, & Isnawati, ; Oluba, Oredokun‐Lache, & Odutuga, ). Astuti et al () studied coconut and black‐eyed pea addition into cassava products.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that cassava processing and the addition of coconut and black‐eyed pea had significant effects to reduce glycemic index compared to a conventional steamed cassava product. Oluba, Oredokun‐Lache, and Odutuga () reported on two different varieties of cassava in Nigeria (white gari and yellow gari) and found that the yellow gari variety had a lower glycemic index.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin A deficiency (VAD) in Ghana is estimated to affect ~20% of children with higher prevalence (31%) in the deprived rural Northern Ghana ( 10 ). Although other factors, such as infections, contribute to VAD, poor dietary intake of vitamin A–rich foods is reported to be the leading cause ( 11 , 12 ). This nutritional cause of VAD is particularly predominant among the poor because of lack of food diversification and unaffordability of some vitamin A–rich foods, such as carrots and liver ( 11 ).…”
Section: Introductionmentioning
confidence: 99%